Impactos eco-hidrológicos do uso e ocupação do solo em região semiárida: o caso da bacia do rio Acaraú, CE - Santos, Cledeilson Pereira (2013)
The knowledge of the relationship between ecological and hydrological processes in semiarid regions is essential for the conservation of river ecosystems because historically, man has established activities near of stream courses and consequently, the use and occupation, well as the multiple uses water. The multiple water uses have changed the dynamics of water in the hydrological cycle, affecting directly river ecosystems, by modifying habitats and encourage behaviors in several species of fauna and flora. Currently, quantification of the land use coupled flow variation has been used to indicate conditions of fluvial ecosystems in the world. It is in this context that the present study evaluates qualitatively the ecohydrological impacts of the land use in the Acaraú river in the state of Ceará, considering statistics that describing five aspects of the flow regime (magnitude, duration, timing of annual, rate and frequency of water). Based on the results obtained, were verified ecohydrological changes ranging from low to medium impact, mainly on aspects such magnitude, period of occurrence of extreme events and gradient flows.